Dhr1p, a Putative DEAH-Box RNA Helicase, Is Associated with the Box C+D snoRNP U3 - Colley, Alan (American Society for Microbiology, 2000)
Putative RNA helicases are involved in most aspects of gene expression. All previously characterized members of the DEAH-box family of putative RNA helicases are involved in pre-mRNA splicing. Here we report the analysis of two novel DEAH-box RNA helicases, Dhr1p and Dhr2p, that were found to be predominantly nucleolar. Both genes are essential for viability, and MET-regulated alleles were therefore created. Depletion of Dhr1p or Dhr2p had no detectable effect on pre-mRNA splicing in vivo or in vitro. Both Dhr1p and Dhr2p were, however, required for 18S rRNA synthesis. Depletion of Dhr2p inhibited pre-rRNA cleavage at sites A(0), A(1), and A(2), while Dhr1p depletion inhibited cleavage at sites A(1) and A(2). No coprecipitation of snoRNAs was detected with ProtA-Dhr2p, but Dhr1p-ProtA was stably associated with the U3 snoRNA. Depletion of Dhr1p inhibited processing steps that require base pairing of U3 to the 5′ end of the 18S rRNA. We speculate that Dhr1p is targeted to the preribosomal particles by the U3-18S rRNA interaction and is required for the structural reorganization of the rRNA during formation of the central pseudoknot.